High-performance inductive couplers based on novel Ce3+ and Co2+ ions co-doped Ni-Zn ferrites. Issue 11 (1st August 2019) - Yang, Pao; Liu, Zhiqing; Qi, Hongbin; Peng, Zhijian; Fu, Xiuli
Abstract: High-performance inductive couplers require Ni-Zn ferrites of high saturation magnetization, Curie temperature, permeability and application frequency. However, for inductive couplers some of these properties run against each other in one ferrite. To balance these requirements, in this work, novel Ni-Zn ferrite ceramics co-doped by Ce 3+ and Co 2+ ions with chemical formula Ni0.4 Zn0.5 Co0.1 Ce x Fe2-x O4 ( x  = 0–0.06) were designed and fabricated by a molten salt method. For the acquired ferrites, both Ce 3+ and Co 2+ ions could come into the lattices. The initially doped Co 2+ ions would cause a slightly decreased grain size and dramatically reduced the specimen densification, but the further added Ce 3+ ions could effectively inhibit the density reduction, while the grain size continues to dwindle. The additional Ce 3+ ions would generate a foreign CeO2 phase in the acquired specimens. The sole doping of Co 2+ ions would aggrandize the saturation magnetization of ferrites, but the introduction of Ce 3+ ions would cause its decrease. However, with an appropriate doping level, the Ce 3+ and Co 2+ ions co-doped ferrites could preserve a relatively high saturation magnetization, while the Curie temperature and cut-off frequency of the ferrites are dramatically augmented, although the permeability would be somewhat reduced. The as-acquired ferrites were simulated to apply in inductive couplers, revealing that the devices manufactured by the Ni0.4 Zn0.5 Co0.1 Ce x Fe2-x O4 ferrites had significantly high maximum operating frequency, compared with that of the one manufactured by pure Ni0.5 Zn0.5 Fe2 O4 ferrite.